2011
DOI: 10.1002/cbdv.201000088
|View full text |Cite
|
Sign up to set email alerts
|

Myrtus communis Berry Color Morphs: A Comparative Analysis of Essential Oils, Fatty Acids, Phenolic Compounds, and Antioxidant Activities

Abstract: Extracts of mature dark blue and white berries from two Tunisian Myrtus communis morphs growing at the same site were assessed for their essential-oil and fatty-acid compositions, phenolic contents, and antioxidant activities. The GC and GC/MS analyses of the essential oils allowed the identification of 33 constituents. The oils from the dark blue fruits showed high percentages of α-pinene (11.1%), linalool (11.6%), α-terpineol (15.7%), methyl eugenol (6.2%), and geraniol (3.7%). Myrtenyl acetate (20.3%) was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
3
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 34 publications
(27 reference statements)
0
58
3
3
Order By: Relevance
“…Secondly, the diversity captured by cultivars needs to be defined in order to inform future breeding strategy, and thirdly, the evaluation of genetic diversity is a major component of any ex situ conservation programme (Pressey et al 2007). A deal of information has been assembled with respect to the biology of the myrtle plant and its chemical composition (Mulas and Fadda, 2004;Fadda and Mulas, 2010;Messaoud and Boussaid, 2011;Mulas et al 2013). A comparison of myrtle populations present in Sardinia and Corsica has suggested that they are rather homogeneous, suggesting a significant amount of gene flow between these neighbouring Mediterranean islands (Migliore et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the diversity captured by cultivars needs to be defined in order to inform future breeding strategy, and thirdly, the evaluation of genetic diversity is a major component of any ex situ conservation programme (Pressey et al 2007). A deal of information has been assembled with respect to the biology of the myrtle plant and its chemical composition (Mulas and Fadda, 2004;Fadda and Mulas, 2010;Messaoud and Boussaid, 2011;Mulas et al 2013). A comparison of myrtle populations present in Sardinia and Corsica has suggested that they are rather homogeneous, suggesting a significant amount of gene flow between these neighbouring Mediterranean islands (Migliore et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations were also reported earlier. [1821] Results of the preliminary phytochemical screening are depicted in Table 2. Powdered drug was treated with different reagents and examined under UV light.…”
Section: Resultsmentioning
confidence: 99%
“…Results of the present study are in agreement with the observations earlier reported. [421] HPTLC (High Performance Thin Layer Chromatography) is an important parameter, which is helpful in the purity and identification of drugs. It is usually quicker and gives better separation.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, lactoferrin, a whey protein has been shown to provide anti-inflammatory effects against colitis induced by dextran sulphate sodium (DSS) in mice (Haversen et al, 2003). More importantly, supplementation myrtle berries to milk improves its anti-inflammatory properties, seen the wealth of myrtle berries of chemical compounds known by their anti-ulcer and antiinflammatory effects (Jabri et al, 2015;Messaoud and Boussaid 2011;Sumbul et al, 2010). In this context several studies have shown the importance of fruit supplementation to dairy products in their improvement much as functional beverages (Zulueta et al, 2007;Cilla et al, 2012;Zulueta et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione regulates the ROS level in the cells; it acts as a growth factor, an antiapoptotic factor in leukocytes and is involved in the cytokine secretion regulation (Sprietsma 1999). The addition of myrtle in bovine milk improved its antioxidant power, in fact a broad range of phenolic compounds has been identified in the myrtle berries (Messaoud and Boussaid 2011) and seeds (Jabri et al, 2015). Polyphenols are the most abundant antioxidants in our diets.…”
Section: Discussionmentioning
confidence: 99%